Determination of Ploidy Levels of Shallot and Japanese Bunching Onion by Flow Cytometry - Endang Sulistyaningsih; Yosuke Tashiro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2003)
-